Quantitative target and systematic non-target analysis of polar organic micro-pollutants along the river Rhine using high-resolution mass-spectrometry – Identification of unknown sources and compounds. (15th December 2015) - Ruff, Matthias; Mueller, Miriam S.; Loos, Martin; Singer, Heinz P.
Abstract: In this study, the contamination by polar organic pollutants was investigated along the Rhine River, an important source of drinking water for 22 million people in central Europe. Following the flow of the river, a traveling water mass was sampled using weekly flow-proportional composite samples at ten different downstream sites, including main tributaries. Using a broad analytical method based on solid phase extraction and high-resolution mass spectrometry, the water was analyzed for more than 300 target substances. While the water in Lake Constance contained only 83 substances in often low concentrations, the number of detects found in the water phase increased to 143 substances and a weekly load of more than 7 tons at the last sampling site, the Dutch-German border. Mostly present were chemicals originating from wastewater treatment plants, especially the artificial sweetener Acesulfam and two pharmaceuticals, Metformin and Gabapentin, which dominate the weekly load up to 58%. Although the sample campaign was performed in a dry period in early spring, a large variety of pesticides and biocides were detected. Several industrial point sources were identified along the waterway's 900 km journey, resulting in high concentrations in the tributaries and loads of up to 160 kg. Additionally, an unbiased non-target analysis was performed following two different strategies for the prioritization of hundreds of potentially relevant unknown masses. While for the first prioritization strategy, only chlorinated compounds were extracted from the mass spectrometer datasets, the second prioritization strategy was performed using a systematic reduction approach between the different sampling sites. Among others, two substances that never had been detected before in this river, namely, the muscle relaxant Tizanidine and the solvent 1, 3-Dimethyl-2-imidazolidinone (DMI), were identified and confirmed, and their loads were roughly estimated along the river. Graphical abstract: Highlights: Comprehensive study to review the contamination along an important river system. More than 130 polar organic micro-pollutants were detected and loads determined. The spatial sampling concept allowed for detection of several point sources. Two approaches for non-target prioritization and identification were implemented. Seven non-targeted compounds were confirmed.